Interactive and sex‐specific life‐history responses of Culex pipiens mosquito larvae to multiple environmental factors. (11th September 2018) - Alcalay, Y.; Puzhevsky, D.; Tsurim, I.; Scharf, I.; Ovadia, O.
Abstract: Spatio‐temporal variation in aquatic habitat characteristics can have important implications for the population and community dynamics of organisms utilizing these habitats. We studied the life‐history responses of Culex pipiens larvae (Diptera: Culicidae) to multiple environmental factors associated with habitat drying by increasing larval density (directly affecting resource availability), temperature fluctuations (influencing physiological processes), and solute concentration due to evaporation (inducing an environmental stress), using a full‐factorial design. We found that high density led to lower larval survival and to shorter development time. Larvae delayed their metamorphosis in response to fluctuating temperature. We detected inter‐sexual differences in the effects of these two factors on adult body sizes, with high larval density leading to the emergence of smaller females, and fluctuating temperature translating to larger adult males. The two sexes also differed concerning the two‐way interactive effects of different environmental factors on development time and on adult size. Our findings indicate that C. pipiens larvae respond to multiple environmental factors via phenotypic plasticity, rather than through bet‐hedging. Future studies should account for additional inter‐stage effects, rather than body size, such as adult fecundity, longevity, and dispersal. Abstract : Life history traits are influenced by both biotic and abiotic conditions and by the degree to which these environmental factors vary in space and over time. Here we show that larvae of the common house mosquito display interactive and sex‐specific life‐history responses to multiple environmental factors associated with the drying of their aquatic habitats. Such responses can have important implications for the population dynamics of the common house mosquito, and for the various diseases it can potentiality transmit.